PERAN STAKEHOLDERS DALAM MENINGKATKAN MUTU PENDIDIKAN MELALUI PENGEMBANGAN EVALUASI KURIKULUM PRODI SASTRA AGAMA DAN PENDIDIKAN BAHASA BALI - Made Susila Putra (Subasita: Jurnal Sastra Agama dan Pendidikan Bahasa Bali, 2021)
This paper is intended to provide an overview about the participation of stakeholders in improving the quality of education, especially providing input in the curriculum evaluation for Religious Literature and Balinese Language Education Program. The demands on higher education (college) are now wider, not only in terms of quantity and academic standards, but also the entire higher education program must prove their quality or quality of its education. To meet the demands of improving the quality of education, there are three factors that must be given attention, namely hardware which consists of facilities and infrastructure, human ware which consists of educators and education staff, and software consisting of curriculum and teaching methods. The curriculum is a very important starting point in realizing the quality of education. Through the curriculum evaluation which involves the participation of stakeholders, they are expected to provide input on improving the quality of education. But in reality the involvement of stakeholders in curriculum evaluation is still lacking, therefore it is necessary to study the active role of stakeholders in their participation in the curriculum evaluation process. The three stakeholders, namely the government, society and educational institutions, have a very big role in developing the curriculum for the Religious Literature and Balinese Language Education Program, STAHN Mpu Kuturan Singaraja through curriculum evaluation.Keywords: stakeholders, education quality, curriculum evaluation.